MENCIPTAKAN TOKO ONLINE YANG MENARIK BAGI SMK PUTRA PERTIWI - Arafat, Muhammad Yasser; Agustian, Bobi; Hidayati, Tri (Universitas Pamulang, 2026)
In today’s digital era, the existence of an e-commerce platform is crucial for vocational educational institutions to market student-made products and serve as a medium for digital entrepreneurship learning. SMK Putra Pertiwi possesses significant potential in creative products but remains constrained by market reach and online visual product presentation. This program aims to create an attractive and professional online store using the WordPress platform supported by the WooCommerce plugin. The implementation methods include needs analysis, responsive interface design (UI/UX), and content management training for staff and students. The output of this program is a functional, aesthetic, and easily manageable online store website. Through this initiative, SMK Putra Pertiwi is expected to enhance its digital competitiveness, expand marketing reach, and provide practical experience for students in managing a digital business ecosystem. Keywords: Online Store, WordPress, SMK Putra Pertiwi, E-commerce, Digital Entrepreneurship